Effect of chronic lung diseases on mortality of prevariant COVID-19 pneumonia patients - Kilic, Hatice; Arguder, Emine; Karalezli, Aysegul; Unsal, Ebru; Guner, Rahmet; Kayaslan, Bircan; Hasanoglu, İmran and Ates, İhsan and Civak, Musa and Akpınar, Esmehan and Parlak, Ebru and Sadi, Filiz and Kocaman, Yasin and Günay, Sibel and Metan, Esra and Er, Mukremin and Dalkıran, Aynil and Hezer, Habibe and Ergüden, Hülya and Hancıoğlu, Zeynep and Kalem, Ayşe and Eser, Fatma and Aypak, Adalet and Akıncı, Esragül and Karahmetoğlu, Selma and Gemcioglu, Emin and Kalkan, Emra and İnan, Osman and Yilmaz, Abdulrezzak and Güler, Bagdagul and Çopuroğlu, Esra and Turan, İşil and; en, Derya and; e, Serhat and; l, Aziz Ahmet (Frontiers in Medicine, 2022)
BACKGROUND: The aim of the study is to assess the effect of chronic lung disease on mortality in patients hospitalized with the diagnosis of prevariant COVID-19 Pneumonia compared to patients without chronic lung disease. RESEARCH DESİGN AND METHODS: A cohort of 1549 patients admitted to the pandemic clinic with a COVID-19 Pneumonia diagnosis were analyzed. Group 1 and Group 2 were compared in terms of the treatment they received, admission to intensive care, mortality and follow-up parameters. RESULTS: The patient group with COVID-19 and lung disease consisted of 231 participants (14.91%) (Group 1). The patient group with COVID-19 but without lung disease had 1318 participants (85.19%). Group 1 cases were found to receive more oxygen therapy and mechanical ventilation than Group 2 cases [p=<0.001], Following univariate and multiple logistic regression analyses, it was determined that patients with chronic lung disease had a 25.76% higher mortality risk [OR: 25.763, 95% CI (Lower-Upper) (2.445-271.465), p=0.007]. CONCLUSION: It was found that chronic lung disease contributed significantly to mortality in this study. Among chronic lung diseases, COPD, lung cancer and interstitial lung diseases were shown to be more effective than other chronic lung diseases in pateints with prevariant COVİD-19 population.